2015
DOI: 10.1016/j.amepre.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Young Adult Sexual Minorities in the U.S.

Abstract: Background Emerging research suggests that young adult sexual minorities (identifying as lesbian, gay, or bisexual or engaging in same-sex attractions or behaviors) experience poorer health than their majority counterparts, but many measures of health inequity remain unexamined in population-based research. Purpose To describe a wide range of health status and healthcare access characteristics of sexual minorities in comparison with those of the majority population in a national sample of U.S. young adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 43 publications
5
55
0
1
Order By: Relevance
“…Currently, it is unknown whether the BMI trajectories of SMW from adolescence to adulthood differ from those of their heterosexual peers, as previous studies attempting to identify sexual orientation-related BMI disparities have yielded conflicting results (6, 15, 18). While Strutz et al found no difference in Wave IV BMI between sexual minority versus heterosexual women in the Add Health cohort, Katz-Wise et al identified higher BMIs in White and Latina bisexual women across all Add Health waves, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is unknown whether the BMI trajectories of SMW from adolescence to adulthood differ from those of their heterosexual peers, as previous studies attempting to identify sexual orientation-related BMI disparities have yielded conflicting results (6, 15, 18). While Strutz et al found no difference in Wave IV BMI between sexual minority versus heterosexual women in the Add Health cohort, Katz-Wise et al identified higher BMIs in White and Latina bisexual women across all Add Health waves, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LGBTQ individuals report higher rates of depression, anxiety disorders, suicidality, and suicide attempts (Eliason & Schope, 2001; Mayer et al, 2008; Lehavot & Simoni, 2011; Reisner, White, Bradford, & Mimiaga, 2014) relative to heterosexual and cisgender people. For LGBTQ young adults, their developmental stage and sexual and/or gender identities converge to create a nexus of risk factors and negative health outcomes that augment the health disparities seen in this population (Strutz, Herring, & Halpern, 2015). …”
mentioning
confidence: 99%
“…Sexual minorities, including individuals who identify themselves as lesbian, gay, bisexual and transgender (LGBT) and those who are attracted to individuals of the same sex or same behaviours, are poorly studied in population-based samples with regard to health and inequalities in health 1 . Nevertheless, it is important to emphasise that the access to health care among sexual minorities is not properly explored in the literature.…”
Section: Introductionmentioning
confidence: 99%